Рыцари Звездного замка: повесть / Сергей Сухинов - Сухинов Сергей Стефанович (Чародеи, 2000)
Экземпляры: ф.5 (2003) / Инвентарный номер: 46724 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 91 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445